Membrane metallo‐endopeptidase is dispensable for repair after nerve injury - Cervellini, I; Galino, J; Zhu, N; Fricker, F; Bao, L; Bennett, D (Wiley, 2019)
Membrane metallo‐endopeptidase (MME), also known as neprilysin (NEP), has been of interest for its role in neurodegeneration and pain due to its ability to degrade β‐amyloid and substance‐P, respectively. In addition to its role in the central nervous system, MME has been reported to be expressed in the peripheral system, specifically in the inner and outer border of myelinating fibers, in the Schmidt‐Lantermann cleft and in the paranodes. Recently, mutations of this gene have been associated with Charcot‐Marie‐Tooth Type 2 (CMT2). Peripheral nerve morphometry in mice lacking MME previously showed minor abnormalities in aged animals in comparison to CMT2 patients. We found that MME expression was dysregulated after nerve injury in a Neuregulin‐1 dependent fashion. We therefore explored the hypothesis that MME may have a role in remyelination. In the naïve state in adulthood we did not find any impairment in myelination in MME KO mice. After nerve injury the morphological outcome in MME KO mice was indistinguishable from WT littermates in terms of axon regeneration and remyelination. We did not find any difference in functional motor recovery. There was a significant difference in sensory function, with MME KO mice starting to recover response to mechanical stimuli earlier than WT. The epidermal reinnnervation, however, was unchanged and this altered sensitivity may relate to its known function in cleaving the peptide substance‐P, known to sensitise nociceptors. In conclusion, although MME expression is dysregulated after nerve injury in a NRG1‐dependent manner this gene is dispensable for axon regeneration and remyelination after injury.